2012
DOI: 10.1007/s00125-012-2743-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity with all-cause mortality and incident and prevalent cardiovascular disease among patients with type 1 diabetes: the EURODIAB Prospective Complications Study

Abstract: Aims/hypothesis The aim of this study was to examine the association of physical activity (PA) with all-cause mortality and incident and prevalent cardiovascular disease (CVD) among patients with type 1 diabetes. Methods The EURODIAB Prospective Complications Study is a cohort including 3,250 male and female patients with type 1 diabetes (mean age 32.7±10.2 years) from 16 European countries, of whom 1,880 participated in followup examinations. In analysis 1 (longitudinal), the association of baseline PA (based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 45 publications
(49 reference statements)
3
58
1
Order By: Relevance
“…Meanwhile, studies have clearly shown that people with type 1 diabetes do not undertake sufficient exercise [64], and that exercise is not actively promoted or supported at the time of diagnosis with type 1 diabetes (unpublished work from our group, N. Lascar, S. Greenfield). The reasons for this are multi-factorial and complex, and include patient anxieties relating to hypoglycaemia and loss of control over their diabetes [65].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, studies have clearly shown that people with type 1 diabetes do not undertake sufficient exercise [64], and that exercise is not actively promoted or supported at the time of diagnosis with type 1 diabetes (unpublished work from our group, N. Lascar, S. Greenfield). The reasons for this are multi-factorial and complex, and include patient anxieties relating to hypoglycaemia and loss of control over their diabetes [65].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity positively affects health status in different types of populations (1)(2)(3)(4)(5)(6)(7)(8)(9). Previous studies in patients with CKD and patients on maintenance hemodialysis (MHD) have shown associations of physical activity with improved outcomes (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Despite early planning, they are often compelled to consume additional carbohydrates, which can lead to excess caloric intake and may increase the risk of subsequent hyperglycaemia [29]. Patients with type 1 diabetes thus face many barriers and rarely meet the recommended physical activity levels, despite the proven health and cardiovascular benefits of exercise [2,3]. In this trial, exercise was not preceded by carbohydrate consumption but was announced to the artificial pancreas algorithm 20 min ahead of the session, which is a practical timing for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is associated with several health benefits for patients with type 1 diabetes such as improved physical fitness, reduced cardiovascular risk factors and reduced insulin requirements [2,3]. Nevertheless, the majority of patients with type 1 diabetes do not meet the recommended physical activity levels mostly because of fear of exerciseinduced hypoglycaemia [4,5].…”
Section: Introductionmentioning
confidence: 99%